The Heirs of Patah Titi in Gayo Community - Jamhir Hasan; Irwansyah Muhammad Jamal; Riza Afrian Mustaqim (Sharia and Law Faculty, 2022)
Inheritance in the Gayo community assumes that grandchildren whose parents have died still have the authority to get inheritance. The solution to this problem has attracted the attention of many people, so it has significant urgency to be investigated. This study aims to explore and analyze; first, how is the inheritance of grandchildren whose parents died first by the heir according to Gayo customary law?, second, how is the settlement of grandchildren whose parents died first from those who bequeath their assets to the Gayo community? This research is an empirical legal research, with a non-doctrinal approach. The data was extracted by observation, interview and documentation methods, then analyzed qualitatively. The results of the study show that first, in general, the Gayo community divides their inheritance based on Islamic inheritance law which is sourced from the teachings of the Qur'an Al-Sunnah. Second, the Gayo community stated that the grandchildren who wore the hijab were given an inheritance divided into three forms; 1) said that he was given a modest inheritance. 2), stated that he was given an inheritance of half of the share received by his parents. 3), stating that the grandson is given an inheritance equal to the share received by his parents. The Gayo community does not know a substitute heir, because there is no stipulation on how much inheritance must be given to the grandson, when receiving an inheritance from his grandparents as a substitute for parents who have died first. Seeing the implementation of giving compensation to grandchildren whose parents died earlier than those who bequeath property to the Gayo community, giving inheritance to grandchildren whose parents died from the heirs does not conflict with Gayo customary law.Waris pada masyarakat Gayo beranggapan bahwa cucu yang telah meninggal orang tuanya masih mempunyai wewenang untuk mendapatkan harta warisan. Penyelesaian persoalan tersebut cukup menyita perhatian banyak kalangan, sehingga memiliki urgensi yang cukup signifikan untuk diteliti. Penelitian ini bertujuan untuk menggali dan menganalisa; pertama, bagaimana kewarisan cucu yang orang tuanya lebih dahulu meninggal oleh pewaris menurut Hukum adat Gayo?, kedua, bagaimana penyelesaian cucu yang orang tuanya lebih dahulu meninggal dari orang yang mewariskan harta pada masyarakat Gayo?. Penelitian ini merupakan penelitian hukum empiris, dengan pendekatan non doktrinal. Data digali dengan metode observasi, wawancara dan dokumentasi, selanjutnya dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa pertama, secara umum masyarakat Gayo membagi warisannya berdasarkan hukum kewarisan Islam yang bersumber dari ajaran Al-Qur'an Al-Sunnah. Kedua, masyarakat Gayo menyatakan bahwa cucu yang terhijab patah titi diberikan harta pusaka dengan pembagian dalam tiga bentuk; 1) mengatakan diberi harta warisan sekedarnya saja. 2), menyatakan diberi warisan setengah dari bahagian yang diterima orang tuanya. 3), menyatakan cucu tersebut diberi harta warisan sebesar bahagian yang diterima orang tuanya. Masyarakat Gayo tidak mengenal ahli waris pengganti, sebab tidak ada ketentuan berapa besar harta warisan yang harus diberikan kepada cucu tersebut, ketika menerina warisan dari kakek/neneknya sebagai pengganti orang tua yang telah meninggal lebih dulu. Melihat pelaksanaan pemberian imbal kasih kepada cucu yang orang tuanya lebih dahulu meninggal dari orang yang mewariskan harta pada masyarakat Gayo maka pemberian harta warisan kepada cucu yang orang tuanya terlebih dahulu meninggal dari pewaris tidak bertentangan dengan Hukum adat Gayo.